Improved adulticidal activity against Aedes aegypti (L.) and Aedes albopictus (Skuse) from synergy between Cinnamomum spp. essential oils - Jirapon Aungtikun; Mayura Soonwera (My University, 2021)
Abstract Improved natural adulticidal agents against mosquito vectors are in urgent need, and essential oils from Cinnamomum plants can assume this role quite readily. Cinnamomum verum , C . cassia , and C . loureiroi essential oils (EOs) were extracted from the barks and evaluated for their chemical composition by GC–MS. The major constituent of the three EOs was cinnamaldehyde. WHO susceptibility tests on individual and combined EOs as well as cinnamaldehyde were conducted against female adults of Aedes aegypti and Aedes albopictus. All EO combinations exhibited a synergistic effect, manifesting a higher toxicity, with a synergistic value ranging from 2.9 to 6.7. Their increasing mortality value was improved between 16.0 to 41.7%. The highest synergistic effect was achieved by an EO combination of 0.5% C . cassia + 0.5% C . loureiroi , while the highest insecticidal activity was achieved by 2.5% C . verum + 2.5% C . cassia and 1% cinnamaldehyde, with a knockdown and mortality rate of 100% and a KT 50 between 0.7 and 2.1 min. This combination was more toxic to both mosquito species than 1% w/v cypermethrin. These findings demonstrate that cinnamaldehyde and synergistic combinations of C . verum + C . cassia EOs and C . cassia + C . loureiroi EOs have a high insecticidal efficacy against Aedes populations.
Keywords: Cinnamomum; Aedes albopictus; Insect Pest Control Strategies